2010
DOI: 10.1021/la103960q
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Properties of Self-Assembled Monolayers by Substrate Curvature

Abstract: Properties of self-assembled monolayers (SAMs) can be tailored by the curvature of the underlying surface. This is so because on a curved support the density of SAM headgroups is always smaller than that of the surface-attachment sites. This density difference increases with increasing curvature and is most pronounced for SAMs formed on nanoscopic particles. This Perspective describes systems in which nanoscale curvature causes pronounced changes in the pK(a) of acid-presenting SAMs or in the electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 121 publications
0
41
0
Order By: Relevance
“…Grzybowski and co‐workers have reported that the pKa of carboxylic acids bound to a nanoparticle surface is dependent on its curvature. In other words, even with the same chemical structure, the chemical properties of ligands can be changed depending on the curvature of the nanoparticle to which the ligands bind . Previously, we have also reported curvature‐dependent thermoresponsivity on gold nanosphere (GNS) assemblies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grzybowski and co‐workers have reported that the pKa of carboxylic acids bound to a nanoparticle surface is dependent on its curvature. In other words, even with the same chemical structure, the chemical properties of ligands can be changed depending on the curvature of the nanoparticle to which the ligands bind . Previously, we have also reported curvature‐dependent thermoresponsivity on gold nanosphere (GNS) assemblies .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, even with the same chemical structure, the chemical properties of ligands can be changed depending on the curvature of the nanoparticle to which the ligands bind. [48,49] Previously, we have also reported curvature-dependent thermoresponsivity on gold nanosphere (GNS) assemblies. [50] The GNSs covered with alkyl-headed hexa(ethylene glycol) (HEG) derivatives (Figure 1a) showed reversible thermoresponsive assembly behavior driven by the dehydration of the HEG part.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Several examples of functionalizing particles in this way exist in the literature. [14][15][16][17][18][19][20] For example, as 40 detailed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, complexity is one of the most exciting aspects of these multicomponent systems, presenting possibilities that just do not exist in the solution‐phase molecular world. Protonation state of surface‐bound species is an ostensibly simple parameter that can have a profound effect on NP properties (Section 2), yet the nanoscale environment provides unique opportunities for controlling NP surface charge . For example, exploiting the effect of local surface curvature on p K a , distinct charge ‘patches’ can be created on nonspherical NPs bearing an otherwise compositionally uniform monolayer .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%